The impact of exercise self-efficacy on college students’ emotion management ability: an analysis of the mediating effects based on exercise behavior and screen media use - Zhu, Weidong; Li, Bo; Lou, Hu; Mu, Fanzheng; Liu, Jun (Frontiers in Public Health, 2024)
Objective: To explore the impact of exercise self-efficacy on college students' emotion management ability and to analyze the mediating effects of exercise behavior and screen media use between exercise self-efficacy and emotion management ability.Methods: This study adopted stratified, whole-cluster, and staged sampling methods, using an online questionnaire that included demographic information, exercise self-efficacy, exercise behavior, screen media use, and other relevant aspects, obtaining a total of 12,687 valid questionnaires.The study indicated a significant positive correlation between exercise self-efficacy and emotion management ability (r = 0.349, P < 0.01). There was also a positive correlation between physical exercise and emotion management ability (r = 0.128, P < 0.01). In contrast, smartphone use showed a significant negative correlation with emotion management ability (r = -0.102, P < 0.01). Additionally, exercise persistence and electronic health literacy presented significant positive